KEPENTINGAN EKONOMI POLITIK INDONESIA DALAM SEKTOR EKSPOR BABI KE SINGAPURA TAHUN 2012-2016 - Paulus Hosbil Romanto; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research is a political economy which explain the efforts to Indonesia from export activities to Singapore in 2012-2016. The activities of pork export from Indonesia has been going since 1986. This export activities is began because the policy of Singapore Government to close all the pork farm due the environmental issue and limited land.Singapore is a state which has a small land, this makes Singapore the main market for agrarian countries to send their agricultural products to Singapore. The existence Indonesia as an agricultural producing country giving an efforts to Indonesia to fill other countries needs about agriculture.This research uses neo-liberalism as the perspective. This perspective explains how to meet human needs with the state as a main actor. The sources in this study were obtained from interviews, library research and internet research. The export of pork from Indonesia to Singapore expected to become a superior commodity in export world.Key words : Swine, Pork, Export, Import, Singapore